Artificial Intelligence in Arbitration: Opportunities and Regulatory Challenges - Quintão, Heider Cristian Moura; de Oliveira Dias, Murillo (Archives of Business Research, 2025)
Recently, new guidelines on the use of Artificial Intelligence (AI) in arbitration marked a significant development in the evolving landscape of the dispute resolution process. In this article, we reviewed those guidelines, comparing historical development of AI integration in arbitral practice and examines key concepts behind these guidelines, with a particular focus on compliance, ethical responsibilities, and confidentiality. The examination of the results placed in perspective procedures for safeguarding procedural fairness, highlighting the autonomy of decision-making authority. The paper also discloses best managerial practices on the use of AI in arbitration, including compliance, preservation of the integrity of proceedings, and avoidance of the misuse of private information. The study offers guidance to scholars, managers, decision-makers and practitioners, in addressing the sophisticated ethical and regulatory challenges of AI in arbitration, setting the foundation for policymaking and future research on this fast-moving practice area.